Obsessive-compulsive symptoms and overall psychopathology in psychotic disorders: longitudinal assessment of patients and siblings - Schirmbeck, Frederike; Swets, Marije; Meijer, Carin J.; Zink, Mathias; de Haan, Lieuwe; Kahn, René S.; Os, Jim van; Bruggeman, Richard; Cahn, Wiepke; Bartels-Velthuis, Agna A. (European archives of psychiatry and clinical neuroscience, 2016)
The course of obsessive-compulsive symptoms (OCS) and its association with alterations in other clinical variables in patients with psychotic disorders is insufficiently known. Patients (n = 602) and unaffected siblings (n = 652) from the Dutch Genetic Risk and Outcome of Psychosis (GROUP) study were investigated at baseline and after 3 years. Participants were assigned to four groups based on the course of OCS over time: no-OCS, persistent OCS, initial OCS and de novo OCS. In addition to cross-sectional comparisons, longitudinal associations between changes in OCS and symptoms of schizophrenia and general functioning were investigated. Patients with co-occurring OCS reported significantly higher severity of psychotic and affective symptoms as well as lower overall functioning compared to patients without OCS. These differences were stable over time for patients reporting persistent OCS. Subsequent repeated measure analysis revealed significant interaction effects for groups reporting changes in their OCS. Whereas the group with remission of initial OCS showed significant improvement in positive symptoms, emotional distress and functioning, the de novo group showed no significant change in these variables, but rather reported stable higher psychopathology. Similar results were found on a subclinical level in siblings. Patients with co-occurring OCS present a more severe clinical picture, especially if symptoms persist over time. The remission of OCS was associated with overall improvement, whereas individuals with de novo OCS already reported higher clinical impairment before OCS onset. More research is needed to elucidate causal pathways and to develop effective interventions for persistent comorbid OCS.